2019
DOI: 10.1515/nleng-2017-0109
|View full text |Cite
|
Sign up to set email alerts
|

MHD stagnation point slip flow due to a non-linearly moving surface with effect of non-uniform heat source

Abstract: In this paper, we have studied the heat transfer characteristics of stagnation point flow of an MHD flow over a non-linearly moving plate with momentum and thermal slip effects in presence of non-uniform heat source/sink. The governing differential equations are transformed into the ordinary differential equations using suitable similarity transformations. These equations which are BVPs’ and are solved using a numerically by fourth order Runge-Kutta method using MAPLE computing software. The effects of governi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…By using the shooting method, numerically solve the system of ordinary differential Equations (10)- (14) with the boundary conditions (15) and (16). The Runge-Kutta method is more capable and proficient than other numerical methods as HPM, FDM, HPM, etc.…”
Section: Implementation Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the shooting method, numerically solve the system of ordinary differential Equations (10)- (14) with the boundary conditions (15) and (16). The Runge-Kutta method is more capable and proficient than other numerical methods as HPM, FDM, HPM, etc.…”
Section: Implementation Of Methodsmentioning
confidence: 99%
“…Malarselvi et al [14] accomplished the investigation on time-dependent MHD flow for several parameters over a flat surface. Nandeppanavar et al [15] investigated that no stagnation point flow consisting of viscous fluid and heat transfer along with velocity due to the moving surface. Baag [16] and his coworkers described the flow analysis and heat transfer analysis past a porous medium in the presence of heat source.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increasing the thermal slip parameter induces decreases in the transfer rates of heat and mass. Nandeppanavar et al, [25] investigated MHD stagnation point flow over a nonlinearly moving plate with momentum and thermal slip effects also non-uniform heat source or sink. Results showed that the velocity slip parameter reduces the flow, velocity and skin friction of the boundary layer but increases the thermal boundary layer, while the temperatures slip parameter decreases the thermal boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of entropy generation was also examined. A research done by Nandeppanavar et al, [12] regarding the heat transfer characteristics of the stagnation point flow of MHD flow over a non-linearly moving plate with momentum and thermal slip effects in the presence of non-uniform heat source showed that the non-uniform heat source parameters enhance the temperature distribution.…”
Section: Introductionmentioning
confidence: 99%